Optimalisasi Wisata Edukasi TPA Pakusari untuk Peningkatan Pembangunan Ekonomi Masyarakat Desa Kertosari, Kab. Jember - Siska Leli Mardiana; Hidayatul Laeli; Dzikrillah Ishaq J (Institut Agama Islam Negeri Jember, 2021)
Based on the results of observations that have been carried out, this study aims to determine the impact of the development of economic growth in the Kertosari village community with the development of educational tours in the Pakusari TPA area. With this Pakusari TPA Educational tour, it is hoped that it will be able to help the economy of the Kertosari village community. This study used a qualitative research method, namely the research method, in which the authors attempted to describe and explain the optimization of educational tourism at TPA Pakusari to improve the economic development of the Kertosari village community. The use of the type of data used for this research is the collection of primary data in the form of data collected related to activities or activities at the Pakusari final disposal site (TPA), as well as interview data with related parties who are directly involved in the educational tourism of the final disposal site (TPA) ) Pakusari with the use of data analysis methods used in the form of descriptive analysis by ensuring which analysis pattern will be used, in this study researchers used non-statistical analysis related to the optimization of Pakusari TPA educational tourism for economic development in Kertosari Village. The results showed that the optimization of educational tourism at TPA Pakusari to improve the economic development of the Kertosari village community had a major impact on the economic growth of the community. It can be seen from government programs such as methane gas. This government program regarding methane gas has been widely felt by the community. With the existence of this TPA educational tour, it is also able to increase the opinion of the Kertosari village community.